Diagnosis and management of asthma, COPD and asthma‐COPD overlap among primary care physicians and respiratory/allergy specialists: A global survey. (24th March 2019) - Jenkins, Christine; FitzGerald, J. Mark; Martinez, Fernando J.; Postma, Dirkje S.; Rennard, Stephen; van der Molen, Thys; Gardev, Asparuh; Genofre, Eduardo; Calverley, Peter
Abstract: Introduction: Asthma‐chronic obstructive pulmonary disease (COPD) overlap (ACO) is a heterogenous condition with clinical features shared by both asthma and COPD. Objectives: This online global survey of respiratory/allergy specialists and primary care practitioners (PCPs) was performed to understand current clinical approaches to the differential diagnosis and management of asthma, COPD and ACO. Methods: Respondents were recruited through: (a) a global online physician respondent community (49, 980 PCPs and 7205 specialists); (b) market research agents; (c) experts; (d) professional societies; (e) colleague invitation. Respondents were presented with a survey including hypothetical clinical scenarios of diagnostic uncertainty to identify management approaches. Results: 891 responses (447 PCPs and 444 specialists) were collected across 13 countries. Reported features used for diagnosis of asthma and COPD were consistent with practice guidelines, but there was variability in those selected for ACO diagnosis. Features typically selected by specialists focused on spirometry/history, while PCPs focused on previous treatment/symptoms. Most respondents could correctly diagnose patients with features of ACO; however, features selected for theoretical diagnosis were often different to those selected in the case scenarios. Additionally, treatment selection was often inconsistent with guidelines, with over half of respondents not recommending inhaled corticosteroids in a patient with ACO and dominant features of asthma. Conclusion: While most PCPs and respiratory/allergy specialists can reach a working diagnosis of ACO, there remains uncertainty around which diagnostic features are most important and what constitutes optimal management. It is imperative that clinical studies including patients with ACO are initiated, allowing the generation of evidence‐based management strategies.